Validation of Thomas Formula in Estimation of Pre-Pregnancy Weight in Bogor City, Indonesia - Siregar, Mukhlidah Hanun; Hardinsyah, Hardinsyah; Roosita, Katrin; Santoso, Budi Iman (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Accurate pre-pregnancy weight is crucial for optimal pregnancy outcomes. However, self-reported pre-pregnancy weight often differs from estimated values owing to various factors. This study aimed to compare pre-pregnancy weight with the self-reported method and estimated using the Thomas formula in pregnant women in Bogor, Indonesia. This cross-sectional study was conducted among 160 pregnant women in Bogor. Pre-pregnancy weight was assessed using both self-reported and the Thomas formula estimation. Differences between the two methods were analyzed using the Wilcoxon Signed-Rank Test. Our study revealed a significant median difference between self-reported and estimated pre-pregnancy weight, with 56.5 kg and 58.4 kg, respectively (pvalue<0.001). Women tended to underestimate their pre-pregnancy weight by -1.7 kg (SD=3.8). There was a difference in the proportion of body mass index (BMI) categories based on self-reported and estimated pre-pregnancy weights. However, the classification of BMI before pregnancy was generally consistent between the two methods. The Thomas formula proved to be more sensitive in predicting the incidence of overweight than underweight in Bogor City. A limitation of this study is that it did not directly validate the measured pre-pregnancy weight, which led to the result that self-reported pre-pregnancy weight may underestimate the actual weight. Although Thomas’s formula provides a precise estimate, it is important to consider the limitations of the self-report and estimation methods. Therefore, healthcare providers should be aware of these differences, use a combination of approaches to assess pre-pregnancy weight, and provide appropriate nutritional counseling